Influence of Economics Teachers Attitude on Attitude and Academic Performance Senior Secondary School Students in Bauchi Zone, Bauchi State - A. Abubakar, Aliyu; E. Istifanus, Dang,; M. Bala , Makson, (Kashere Journal of Education, 2021)
The study is carried out to investigate the impact of economics teachers’ attitude on student’s attitude and academic performance in Bauchi Educational zone, the population of 29,199 senior secondary school two (SSII) students of government owned senior secondary schools their Two hundred and Forty-Five, (245) economics teachers was used. From the population of the study, the sample sizes of 420 students and 21 economics teachers were drawn. The drawing of the sample size was guided by Kreycie and Morgan (1970) table of sampling, the sample was drawn using stratified or multi stage sampling procedure. Three research questions and two null hypotheses were raised to guide the study. The data obtained was analyzed using the appropriate tools and procedure in SPSS version 26. The result revealed a positive relationship between teacher attitude and students’ attitude towards learning Economics. The result also revealed that students’ attitude towards learning of Economic has a significant impact on their academic performance. Among many suggestions and recommendations raised, teachers were advised to build excellent rapport with students and create an attractive and enjoyable environment to ensure students are dynamically involving in the classroom activities so that to arouse their attitudes towards Economics